PENGARUH DISIPLIN PEGAWAI TERHADAP PRESTASI KERJA DI DINAS PERTANIAN PROVINSI SULAWESI UTARA - PUTRA, ARDHIKA ANGGARA; Mandey, Jantje; Rorong, Arie Junus (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Labor discipline is a behavioral containing technical aspects that work ethic is the norms that arebinding and are set explicitly and practices such as behavioral attitudes respect, honor, obey, and obey thatmust be held to be maintained and implemented in government agencies. Problems to be answered in thisstudy is the work discipline of employees about employee performance affects the performance ofemployees working in the department of Agriculture of North Sulawesi. This study aims to determine theeffect of labor discipline against the employees of performance. These results indicate that the labordiscipline and significant positive effect on the productivity of employees in the department of Agricultureof North Sulawesi. Based on these conclusions labor discipline must be observed and maintained on eachemployee so that the tasks and responsibilities can be a priority terselenggarakan well.Keywords: influence, discipline, work performance.